Peningkatan Produktivitas dan Profitabilitas Petani Pisang Barlin di Desa Papringan Kecamatan Temayang Kabupaten Bojonegoro - Putra, Arda Purnama; Pratiwi, Iqlima; Prajogo, Uke (STIE Malangkucecwara, 2024)
Barlin Banana is a leading agricultural products in Bojonegoro. However, the shelflife of Pisang Barlin only 10 days at room temperature. Therefore, a lot of which iswasted because of rotten bananas. As a result, the loss is very large bananagrowers. The selling price of the product is also relatively cheap only around Rp1500 per comb. These conditions led to the welfare of farmers Barlin Banana stilllow. Farmers group Barlin Banana